Economia comportamental e vulnerabilidade cognitiva: fundamentos científicos para a proteção do consumidor no Brasil - Felipe Moreira dos Santos Ferreira (2012)
Based on many research works carried out in the field of Behavioral Economics, this work tried to demonstrate consumers behavior patterns in the market, basically marked by the presence of systematic cognitive mistakes, aiming at exposing a non circumstantial vulnerability capable of providing scientific data to Brazilian Consumer Protection Policies. The initial question arose from the observation that in Brazilian Consumer Law there is a non explicit association between consumer protectionmatters and traditional economic assumptions, what leads to a lower predictive capacity, and consequently, a lower effectiveness of protective policies. For this reason, this paper promoted an approximation of Consumer Law to Behavioral Economics, as to prevent the application of the substantially rational subject model, allowing instead, a reflexion on the real extent of the Principle of Vulnerability, as it has been consolidated by the Brazilian Consumer Law Code. The goal of this research work was to demonstrate consumers vulnerability in face of its real behavior in the market, including the analysis of heuristics, biases and cognitive limitations that gear the decision making process. As way of conclusion, by identifying consumers cognitive vulnerability, which is genuinely not circumstantial, eminently scientific bases were created as fundamentals to Brazilian Consumer Law.